Ogólne rezerwy na straty kredytowe w bankach w świetle prawa bankowego, bilansowego i podatkowego - Orzeszko, Teresa (General loan loss reserves in banks in the light of bank, accounting and tax law, 2007)
The objective of the hereby article is to identify types of general loan loss reserves as well as to analyze and present principles of their functioning in the light of regulations obligatory for the banks which are officially seated in Poland. Having indicated basic legal documents which underlie the regulations in question, the article characterizes the profile of particular general loan loss reserves’ types putting main emphasis on the subject and background of creating them, the rules of their pricing, the time and manner of their increasing and decreasing, but also on the requirements regarding the disclosure of reserves in financial statements.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1186, s. 212-226